Morphological characteristics of Indonesian Rubus flowers - Suluh Normasiwi; Andi Salamah; Muhammad Imam Surya (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Normasiwi S, Salamah A, Surya MI. 2021. Morphological characteristics of Indonesian Rubus flowers. Biodiversitas 22: 1441-1447. Rubus spp. are woody or herbaceous plants that can be used for fruit, ornamental and medicinal purposes. The increasing use of Rubus as a commercial species is highly dependent on the formation of high-quality genetic material. However, the lack of basic biological knowledge is one of the limiting factors in this development. This research aims to describe the morphological characters of Indonesian Rubus flowers at Cibodas Botanical Garden, Indonesian Institute of Sciences, Cianjur, West Java, Indonesia. From January to June 2020, we observed nine Rubus species with five replications, namely R. alceifolius, R. chrysophyllus, R. ellipticus, R. fraxinifolius, R. linneatus, R. moluccanus, R. pyrifolius, R. rosifolius, and Rubus sp (Blackberry) in Cibodas Botanical Garden, Indonesia. The results showed variations in the characteristics of the pistil, stamens, torus shape, and duration of flowering stages between species. The mean value of the stamen-pistil ratio for R. pyrifolius was highest among other species (8.27), and R. fraxinifolius was the lowest (0.16). Furthermore, a correlation analysis between stamens and pistils for nine Rubus species was relatively positive (r = 0.598), similarly distinctly positive between pistils and fruits with r = 0.763. Flower development duration takes ranging 10-12 days from initiation to anthesis, depending on the species.